Designing an Information System for Recording Incoming and Outgoing Goods at the Warehouse of the Engineering Faculty, Universitas Sebelas Maret, Surakarta: Perancangan Sistem Informasi Pencatatan Barang Masuk Dan Barang Keluar Pada Gudang Fakultas Teknik Universitas Sebelas Maret Surakarta - Mudakir, Mudakir; Naury, Chairullah; Santosa, Eka Budhi (RADIANT: Journal of Applied, Social, and Education Studies, 2023)
The Faculty of Engineering, Universitas Sebelas Maret (UNS) in service activities for students requires consumables stored in the warehouse of the Faculty of Engineering, UNS. Every month a document recapitulation is carried out to control the circulation that occurs in the warehouse of the UNS Faculty of Engineering. The document recap system still uses the manual method, namely by recording incoming and outgoing goods to the ledger. Data from the general ledger is copied into the Microsoft Excel application to create a circulation report. The current manual system still has human errors that often occur, such as missing or tucked records of incoming and outgoing goods. This has an impact on when recapitulating the results of the information data obtained is less accurate. Based on the description of the background above, it can be formulated the problem to be solved in this study is "How to design an Information System for Recording Incoming and Outgoing Goods in the Warehouse of the Faculty of Engineering UNS". Limitations The problem that the author discusses in the study focuses more on the process of recapitulating incoming and outgoing goods data, as well as making reports on the circulation of goods within the UNS Faculty of Engineering. The method used to design an information system for recording goods data uses the Software Development Life Cycle (SDLC) with the Waterfall model. The programming language used to design an information system for recording data items is PHP Native and MySQL database as a data storage medium. With the design of this item data recording information system, it is hoped that it will make it easier for the head of the warehouse in terms of ordering goods in accordance with the stock data in the warehouse of the Faculty of Engineering, UNS.